2006
DOI: 10.1029/2005jd006527
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of surface ozone and reactive nitrogen observed at a remote mountain site in the northeastern Qinghai‐Tibetan Plateau, western China

Abstract: [1] Measurements of surface ozone (O 3 ), carbon monoxide (CO), nitric oxide (NO), and total reactive nitrogen (NO y ) were made, in conjunction with other trace gases and fine aerosols, at Mount Waliguan (WLG, 36.28°N, 100.90°E, 3816 m above sea level) in the late spring and summer of 2003 in order to better understand the source(s) of ozone and other chemically active gases over the remote highlands of western China. The average mixing ratio (plus or minus standard deviation) was 58 (±9) ppbv for O 3 , 155 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
132
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(147 citation statements)
references
References 58 publications
13
132
2
Order By: Relevance
“…Our simulated surface-layer concentrations of O 3 are high in both western and eastern China, which agree with the modeling studies of Wang et al (2011), Jeong andPark (2013), and Lou et al (2014). The high O 3 concentrations in western China are associated with the downward transport of O 3 from the stratosphere to troposphere (Wild and Akimoto, 2001;T. Wang et al 2006a;Ding and Wang, 2006), and the high O 3 concentrations in eastern China result from anthropogenic emissions (Wang et al, 2011).…”
Section: East Asian Summer Monsoon Indexsupporting
confidence: 80%
“…Our simulated surface-layer concentrations of O 3 are high in both western and eastern China, which agree with the modeling studies of Wang et al (2011), Jeong andPark (2013), and Lou et al (2014). The high O 3 concentrations in western China are associated with the downward transport of O 3 from the stratosphere to troposphere (Wild and Akimoto, 2001;T. Wang et al 2006a;Ding and Wang, 2006), and the high O 3 concentrations in eastern China result from anthropogenic emissions (Wang et al, 2011).…”
Section: East Asian Summer Monsoon Indexsupporting
confidence: 80%
“…For example, the maximum value at the Waliguan site in the Qinghai-Tibet Plateau (3810 m asl) took place at night or early morning, and there was little diurnal variation. This is caused by the extremely low levels of O 3 precursors in the closed natural background condition (Ma et al, 2002;Wang et al, 2006). The difference in O 3 concentration during the day and night showed that O 3 was produced by local photochemical reactions at this site (Crutzen et al, 1999;Xu et al, 2008).…”
Section: Calculation Of O 3 Concentration-based Indicesmentioning
confidence: 99%
“…Surface ozone at the site has been proved to be highly representative of free-tropospheric ozone (Ma et al, 2002b) and hence is subjected to the influences of STE events (Ding and Wang, 2006;Zhu et al, 2004). Air masses from the west are dominant at WLG and were found to be associated with the highest ozone mixing ratios (Wang et al, 2006b). Only in summer a substantial portion of the airflows comes from the eastern sector and exposes the surface ozone mixing ratio to some regional anthropogenic influences (Wang et al, 2006b;Xue et al, 2011).…”
mentioning
confidence: 99%
“…Air masses from the west are dominant at WLG and were found to be associated with the highest ozone mixing ratios (Wang et al, 2006b). Only in summer a substantial portion of the airflows comes from the eastern sector and exposes the surface ozone mixing ratio to some regional anthropogenic influences (Wang et al, 2006b;Xue et al, 2011). Previous studies of ozone at WLG, based on short-term measurements and modelling results, clarified the causes for certain episodes or for the diurnal and seasonal cycles of ozone (Ma et al, 2002a(Ma et al, , 2005Zhu et al, 2004).…”
mentioning
confidence: 99%